OPTIMIZATION OF NANO GEL FORMULATION BASED ON BANGKAL (NAUCLEA SUBDITA) WOOD BARK EXTRACT AND ANTIBACTERIAL ACTIVITY AGAINST PROPIONIBACTERIUM ACNES - JANAH, HAMIDATUL; YULIANASARI, DHANI SINTA; AZIZAH; FAUZIYAH, NIDA; ANNISA, RIFKA; AHDYANI, RISA (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to formulate and evaluate the antibacterial activity of a nanogel preparation incorporating Bangkal (Nauclea subdita) bark extract against Propionibacterium acnes. Methods: Bangkal bark extract was obtained using a maceration technique with 70% ethanol as the solvent (1:10). The resulting thick extract was then formulated into a nanogel and subjected to stability testing. Antibacterial activity was assessed using the well diffusion method. The nanogel formulation exhibiting the highest inhibition zone underwent particle size analysis using a Particle Size Analyzer (PSA). Bangkal bark was extracted using a maceration technique with 70% ethanol solvent (1:10). The thick extract obtained was then made into nanogels, stability tests were carried out, and its antibacterial activity was tested using the well method. The nanogel with the highest inhibition zone will have its particle size identified using a Particle Size Analyzer (PSA). Results: The Bangkal bark extract nanogel was successfully formulated as a homogenous, thick brown gel with a characteristic extract aroma. PSA analysis revealed a nanoparticle size of 0.995 nm. The antibacterial assay showed effective inhibition of P. acnes, with inhibition zones ranging from 6 to 8 mm. The F3 formulation (8% extract) exhibited the highest antibacterial activity with an 8 mm inhibition zone. Conclusion: This study demonstrates the potential of Bangkal bark extracts in a nanogel formulation for acne treatment. The F3 formulation (8% extract) showed moderate antibacterial activity, suggesting its viability as a natural alternative for acne management. Ethanol as a green solvent supports sustainable and eco-friendly formulation development.